2010
DOI: 10.1016/j.neulet.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Fact or fiction? An event-related potential study of implicit emotion regulation

Abstract: Emotion regulation can be achieved through a number of processes. Previous studies have investigated this issue by encouraging individuals to voluntarily change how they think about a situation in order to decrease its emotional impact. However, little is known about automatic regulation processes. The goal of the present study was to investigate whether an "implicit reappraisal strategy" would modulate the Late Positive Potential (LPP) associated to affective picture viewing. Unpleasant pictures, presented as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 42 publications
8
85
3
1
Order By: Relevance
“…Indeed, emotional pictures are more arousing than emotional faces (Britton, Taylor, Sudheimer, & Liberzon, 2006), and emotional effects on EPN and LPP increase with arousal (Cuthbert et al, 2000;Schupp, Junghöfer, Weike, & Hamm, 2003;Wiens, Sand, & Olofsson, 2011). The evidence is consistent with this explanation because, irrespective of inattention and perceptual load, residual emotional effects on EPN and LPP were found for emotional IAPS (Sand & Wiens, 2011;Wiens, Sand, Norberg, & Andersson, 2011), emotional pictures that participants believed to be real scenes (Mocaiber et al, 2010), and spiders in participants with spider fear (Norberg et al, 2010).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, emotional pictures are more arousing than emotional faces (Britton, Taylor, Sudheimer, & Liberzon, 2006), and emotional effects on EPN and LPP increase with arousal (Cuthbert et al, 2000;Schupp, Junghöfer, Weike, & Hamm, 2003;Wiens, Sand, & Olofsson, 2011). The evidence is consistent with this explanation because, irrespective of inattention and perceptual load, residual emotional effects on EPN and LPP were found for emotional IAPS (Sand & Wiens, 2011;Wiens, Sand, Norberg, & Andersson, 2011), emotional pictures that participants believed to be real scenes (Mocaiber et al, 2010), and spiders in participants with spider fear (Norberg et al, 2010).…”
supporting
confidence: 55%
“…First, when pictures of spiders and mushrooms were shown at fixation and participants performed a task on letters that surrounded the pictures, spider-fearful participants showed a greater LPP to spiders versus mushrooms than did nonfearful participants, even though the pictures were unattended (Norberg, Peira, & Wiens, 2010). Second, when mutilated bodies were shown at fixation and participants performed a matching task on bars to either side of the pictures, there was an emotional effect on LPP when participants believed that the pictures were real (Mocaiber, Pereira, Erthal, Machado-Pinheiro, David, & Cagy, 2010). Third, when negative and neutral IAPS pictures were shown at fixation and participants performed a task on letters that surrounded the pictures, there was an emotional effect on LPP but not on EPN (Wiens, Sand, Norberg, & Andersson, 2011).…”
mentioning
confidence: 99%
“…[71][72][73] Mais especificamente no âmbito alimentar, Grabenhorst, Rolls & Bilderbeck 74 observaram, através da técnica de ressonância magnética funcional, que ativações relacionadas ao valor afetivo do sabor umami na região orbitofrontal (área implicada no processamento de recompensa) podem ser realçadas por textos descritivos apresentados aos participantes. Outro estudo mostrou que participantes expostos a rótulos, que ressaltavam tanto o sabor como os aspectos saudáveis de uma maçã, a selecionaram significativamente mais comparados aos participantes que viram a maçã sem qualquer descritor.…”
Section: -62unclassified
“…Emotional regulation is a fundamental skill for social interaction, directly influencing behavior and emotional expression (Lopes, Salovey, Cote, & Beers, 2005;Mocaiber et al, 2010). Studies have shown that individual differences in the dimensions of positive affect traits , anxiety levels (Mauss, Wilhelm, & Gross, 2003;Gillath, Bunge, Shaver, Wendelken, & Mikulincer, 2005;Mocaiber et al, 2009), prosocial tendencies (Lopes et al, 2005), and hemispheric asymmetry activation profiles (Jackson et al, 2003) influence the ability to regulate emotions.…”
Section: Introductionmentioning
confidence: 99%